Rechokim . The Collaborator and His Family - Barash, Adi; Shatz, Ruthie (Yulari Films, 2011)
Coproduction: France, Israel, USA. Verzio FF A Palestinian informer finds himself and his family trapped when his twenty years of services is not enough to earn a place in Israel. "The Collaborator and His Family" is a chronicle of family, assimilation and espionage that follows the El-Akels, a Palestinian family whose father, Ibrahim, has been a collaborator for ideological reasons with the Israeli security services for 20 years. Branded as traitors by Palestinians, the entire family fled to Israel seeking the asylum that had been promised by Ibrahim's Israeli “operator.” Over a two-and-a-half-year period, as each day passes with no progress towards citizenship, tension builds within the family. Alienated and humiliated, Ibrahim's wife Yusra, three teenage sons and two daughters bear the consequences of Ibrahim's decision while struggling to assimilate into Israeli society. Co-directors Adi Barash and Ruthie Shatz gain intimate access to the hardest moments the family face, observing as each connecting thread between family members unravels. This unflinching documentary highlights the experience of the many who risk their lives to collaborate with the enemy.